De la resistencia a la transformación: una revisión de la resiliencia en el deporte (2021)
A literature review was conducted on the research contributions of resilience in sport between 2010 and 2020 in a sample of 239 articles, which responded to inclusion criteria such as: Original Articles, Literature Review, Qualitative, Quantitative or Mixed Studies published; Thesis or Degree Works and Book Chapters. The search was performed in the following databases: PubMed, Ebsco Host, Science Direct, Scopus, PsyINFO. It was found that research and contributions of resilience in sport are numerous and applied to a great diversity of sport modalities and at the level of physical activity, formative and competitive sport. Quantitative-descriptive studies were predominantly found; however, different methodological approaches are highlighted. It was also observed that the studies were oriented towards adult and adolescent populations, and a third focus of interest is literature reviews. The fields in which resilience in sport was explored were associated with performance in competition, coping with adversity, stressful situations, or Burn Out, as a motivational dimension. It is concluded that it is necessary to carry out specific studies by sport practice, types of sport and related psycho-social phenomena such as the influence of recovery from injuries, moods and adverse extra-sport and extra-competition situations.